Preparation method and application of Pd / CNTs-CeO2 nano-electrocatalyst

By preparing Pd/CNTs-CeO2 nanoelectrocatalysts, the problems of high cost, low activity and inactivation of existing Pt-based catalysts in direct methanol fuel cells are solved, and the efficient and stable methanol electrocatalytic oxidation performance in alkaline environments is achieved.

CN118538939BActive Publication Date: 2025-03-25LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310342348.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-03-25
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

The high cost, low activity, catalyst poisoning and deactivation problems of Pt-based catalysts in existing direct methanol fuel cells limit the commercial application of direct methanol fuel cells.

Method used

Using the preparation method of Pd/CNTs-CeO2 nanoelectrocatalyst, Pd/CNTs-CeO2 nanoelectrocatalyst with high methanol electrocatalytic properties and stability was prepared by ultrasonic dispersing multi-walled carbon nanotubes and soluble cerium salts, adjusting pH value and carrying out hydrothermal reactions.

Benefits of technology

In an alkaline environment, Pd/CNTs-CeO2 nanoelectrocatalysts exhibit good electrocatalytic oxidation performance and stability of methanol, reducing the cost of the catalyst and improving activity, and avoiding the poisoning and inactivation of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118538939B_ABST
    Figure CN118538939B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a Pd / CNTs-CeO2 nano-electrocatalyst, the method comprising: adding multi-walled carbon nanotubes and soluble cerium salts to deionized water, adjusting the pH value after ultrasonic dispersion, washing, drying, grinding, obtaining a mixture precursor, calcining to obtain a CNTs-CeO2 composite carrier, dispersing it in ethylene glycol, then dripping an H2PdCl4 aqueous solution, adjusting the pH value, hydrothermally reacting at 120-170°C, washing with deionized water and anhydrous ethanol, and vacuum drying to obtain a Pd / CNTs-CeO2 nano-electrocatalyst. An application is also provided for the electrocatalytic oxidation of methanol in an alkaline environment. The Pd / CNTs-CeO2 nano-electrocatalyst prepared by the present invention has good electrocatalytic oxidation performance of methanol in an alkaline environment, and has higher methanol electrocatalytic performance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysts, and specifically relates to a preparation method and application of a Pd / CNTs-CeO2 nano electrocatalyst. Background Art

[0002] Direct Methanol Fuel Cells (DMFCs) are energy conversion devices that directly convert the chemical energy of methanol into electrical energy. They have the advantages of both batteries and internal combustion engines, and are NO-free. x and SO x Emissions, the carbon emissions of the whole life cycle can be reduced by 40%, and methanol has the advantages of safe storage and transportation, simple structure, and high specific energy, and has become a key technology included in my country's key development. In March 2019, eight ministries and commissions including the Ministry of Industry and Information Technology, the National Development and Reform Commission, and the Ministry of Science and Technology jointly issued the "Guiding Opinions on the Application of Methanol Vehicles in Some Regions", which pointed out that "enterprises are encouraged and supported to develop methanol fuel cell vehicle products, accelerate the transformation of scientific research results and industrial application of methanol vehicles, and give priority to the application of methanol fuel cell vehicles in the coal-rich areas of the northwest". Therefore, it is urgent to quickly realize the large-scale commercial application of DMFCs.

[0003] Currently, researchers have developed a variety of strategies to prepare efficient Pt-based electrocatalysts. The main strategies can be summarized as preparing multi-metal alloys, synthesizing intermetallic compounds, and constructing catalysts with special composition and morphology. However, effective strategies for preparing efficient electrocatalysts still need further research.

[0004] At present, commercial catalysts for direct methanol fuel cells are still mainly Pt-based catalysts. The main problems in their application are: (1) Pt is a precious metal, which leads to high catalyst costs; (2) low activity due to slow anode kinetics; (3) Pt-based catalysts react with CO generated during methanol oxidation. ads The intermediates have characteristic adsorption, which causes the catalyst to be poisoned. (4) In the acidic alkaline electrolyte environment, the active metal of the catalyst agglomerates and loses, resulting in deactivation. Analyzing the causes of the above problems, it is not difficult to conclude that the development of highly dispersed, highly active and stable Pt-based catalysts is the key to realizing the commercial application of direct methanol. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a Pd / CNTs-CeO2 nano-electrocatalyst and its application in view of the deficiencies of the above-mentioned prior art. The Pd / CNTs-CeO2 nano-electrocatalyst has good electrocatalytic oxidation performance for methanol in an alkaline environment and has higher methanol electrocatalytic performance and stability.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a Pd / CNTs-CeO2 nano-electrocatalyst, the method comprising:

[0007] S1, adding multi-walled carbon nanotubes and soluble cerium salt into deionized water, and ultrasonically dispersing for 60 minutes to obtain a mixed solution;

[0008] S2, adjusting the pH value of the mixed solution obtained in S1 to 11-13 with a 1.0 mol / L KOH aqueous solution, stirring for 2 h, washing with deionized water to neutrality, and then drying under vacuum conditions at a temperature of 65° C. for 12 h, and then grinding to obtain a mixture precursor;

[0009] S3, placing the mixture precursor obtained in S2 into a tube furnace, raising the temperature from room temperature to 250°C to 350°C at a heating rate of 2°C / min under a N2 atmosphere, then calcining at a constant temperature for 2h, and naturally cooling to room temperature to obtain a CNTs-CeO2 composite carrier;

[0010] S4, ultrasonically dispersing the CNTs-CeO2 composite carrier obtained in S3 into ethylene glycol to obtain a carrier mixed solution;

[0011] S5. Add 0.0187 mol / L H2PdCl4 aqueous solution to the carrier mixture obtained in S4, stir for 4 hours, adjust the pH value to 12 with 0.5 mol / L-2 mol / L NaOH aqueous solution, and carry out hydrothermal reaction at 120°C-170°C for 4 hours. After cooling to room temperature, wash with deionized water for 3-4 times, then wash with anhydrous ethanol for 3-4 times, and then dry under vacuum at 70°C for 12 hours to obtain Pd / CNTs-CeO2 nano-electrocatalyst.

[0012] Preferably, the dosage ratio of the multi-walled carbon nanotubes, the soluble cerium salt and the deionized water in the mixed solution in S1 is 0.2 g: (0.5-3.5) g: 12 mL.

[0013] Preferably, the soluble cerium salt in S1 is cerium nitrite or cerium nitrate hexahydrate.

[0014] Preferably, the outer diameter of the mixture precursor in S2 is 8 nm to 15 nm, and the length is ≤50 μm.

[0015] Preferably, the dosage ratio of CNTs-CeO2 carrier and ethylene glycol in the carrier mixed solution in S4 is 50 mg:30 mL.

[0016] Preferably, the average particle size of the Pd / CNTs-CeO2 nano-electrocatalyst in S5 is 3.75 nm to 4.25 nm.

[0017] The present invention also provides the application of the Pd / CNTs-CeO2 nano-electrocatalyst prepared by the above-mentioned preparation method, wherein the Pd / CNTs-CeO2 nano-electrocatalyst is used for the electrocatalytic oxidation of methanol in an alkaline environment.

[0018] Preferably, the potential of the Pd / CNTs-CeO2 nano-electrocatalyst for methanol electrocatalytic oxidation is -0.9V to 0.3V, and the oxidation peak current is 2642.6mA·mg -1 Pd ~3042.5mA·mg -1 Pd .

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. The cerium oxide on the surface of the CNTs-CeO2 composite carrier prepared in the present invention is evenly dispersed, which can provide more anchoring points for the active metal, which is beneficial to improve the effective loading rate of the active metal Pd while ensuring the dispersion; secondly, there is a metal-carrier interaction (MSI) between Pd and CNTs-CeO2, and the cerium oxide adjusts the electronic structure properties of Pd, improving the adsorption and activation characteristics of the catalyst for methanol; at the same time, the composite carrier is also beneficial to promote the dissociation of water in the electrolyte to form adsorbed hydroxyl groups (OH ads ), which is conducive to the oxidation of adsorbed carbon monoxide (CO ads ), can greatly improve the efficiency of direct methanol fuel cells.

[0021] 2. In the CNTs-CeO2 composite carrier prepared by the present invention, cerium oxide is evenly distributed on the carbon nanotubes. The catalyst Pd / CNTs-CeO2 is prepared using the carrier, which has good electrocatalytic oxidation performance for methanol in an alkaline environment, and has higher methanol electrocatalytic performance and stability. The Pd / CNTs-CeO2 nano-electrocatalyst in the present invention can be used as a direct methanol fuel cell anode catalyst in an alkaline environment.

[0022] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is an X-ray diffraction (XRD) diagram of the CNTs-CeO2 composite carrier prepared in step S3 in Example 1 of the present invention.

[0024] Figure 2 This is a transmission electron microscopy (TEM) image of the Pd / CNTs-CeO2 nano-electrocatalyst prepared in Example 1 of the present invention.

[0025] Figure 3This is a cyclic voltammetry (CV) diagram of the Pd / CNTs-CeO2 nano-electrocatalyst prepared in Example 1 of the present invention under 1.0M KOH+1.0M CH3OH (scanning rate 50mV / s, potential range -0.9-0.3V). DETAILED DESCRIPTION

[0026] Example 1

[0027] The preparation method of the Pd / CNTs-CeO2 nano-electrocatalyst of this embodiment is as follows:

[0028] S1, adding 0.2 g of multi-walled carbon nanotubes (MWCNTs) and 0.5 g of soluble cerium salt (cerium nitrite) to 12 mL of deionized water, and ultrasonically dispersing for 60 min to obtain a mixed solution;

[0029] S2, adjusting the pH value of the mixed solution obtained in S1 to 12 with a 1.0 mol / L KOH aqueous solution, stirring for 2 hours, washing with deionized water to neutrality, and then drying for 12 hours under vacuum conditions at a temperature of 65°C, and then grinding to obtain a mixture precursor with an outer diameter of 8 nm to 15 nm and a length of ≤50 μm;

[0030] S3, placing the mixture precursor obtained in S2 into a tube furnace, raising the temperature from room temperature to 300°C at a heating rate of 2°C / min under a N2 atmosphere, then calcining at a constant temperature for 2h, and naturally cooling to room temperature to obtain a CNTs-CeO2 composite carrier;

[0031] S4, ultrasonically dispersing 50 mg of the CNTs-CeO2 composite carrier obtained in S3 into 30 mL of ethylene glycol to obtain a carrier mixed solution;

[0032] S5. To the carrier mixture obtained in S4, 6.25 mL of 0.0187 mol / L H2PdCl4 aqueous solution was added dropwise. After stirring for 4 h, the pH value was adjusted to 12 with 1 mol / L NaOH aqueous solution. The mixture was transferred to a stainless steel kettle containing 100 mL of polytetrafluoroethylene lining and subjected to hydrothermal reaction at 150 °C for 4 h. After cooling to room temperature, the mixture was washed with deionized water for 4 times, and then washed with anhydrous ethanol for 4 times. The mixture was then dried at 70 °C under vacuum for 12 h to obtain a Pd / CNTs-CeO2 nano-electrocatalyst with an average particle size of 3.75 nm, named Pd / CNTs-CeO2-1.

[0033] Example 2

[0034] The preparation method of the Pd / CNTs-CeO2 nano-electrocatalyst of this embodiment is as follows:

[0035] S1, adding 0.2 g of multi-walled carbon nanotubes (MWCNTs) and 2 g of soluble cerium salt (cerium nitrite) into 12 mL of deionized water, and ultrasonically dispersing for 60 min to obtain a mixed solution;

[0036] S2, adjusting the pH value of the mixed solution obtained in S1 to 13 with a 1.0 mol / L KOH aqueous solution, stirring for 2 hours, washing with deionized water to neutrality, and then drying for 12 hours under vacuum conditions at a temperature of 65°C, and then grinding to obtain a mixture precursor with an outer diameter of 8 nm to 15 nm and a length of ≤50 μm;

[0037] S3, placing the mixture precursor obtained in S2 into a tube furnace, raising the temperature from room temperature to 250°C at a heating rate of 2°C / min under a N2 atmosphere, then calcining at a constant temperature for 2h, and naturally cooling to room temperature to obtain a CNTs-CeO2 composite carrier;

[0038] S4, ultrasonically dispersing 50 mg of the CNTs-CeO2 composite carrier obtained in S3 into 30 mL of ethylene glycol to obtain a carrier mixed solution;

[0039] S5. Add 6.25 mL of 0.0187 mol / L H2PdCl4 aqueous solution to the carrier mixture obtained in S4, stir for 4 h, adjust the pH value to 12 with 0.5 mol / L NaOH aqueous solution, transfer to a stainless steel kettle containing 100 mL of polytetrafluoroethylene lining, and perform hydrothermal reaction at 170°C for 4 h. After cooling to room temperature, wash with deionized water for 3 times, then wash with anhydrous ethanol for 3 times, and then dry under vacuum at 70°C for 12 h to obtain a Pd / CNTs-CeO2 nano-electrocatalyst with an average particle size of 4.25 nm, named Pd / CNTs-CeO2-2.

[0040] Example 3

[0041] The preparation method of the Pd / CNTs-CeO2 nano-electrocatalyst of this embodiment is as follows:

[0042] S1, adding 0.2 g of multi-walled carbon nanotubes (MWCNTs) and 3.5 g of soluble cerium salt (cerium nitrite) to 12 mL of deionized water, and ultrasonically dispersing for 60 min to obtain a mixed solution;

[0043] S2, adjusting the pH value of the mixed solution obtained in S1 to 11 with a KOH aqueous solution having a concentration of 1.0 mol / L, stirring for 2 h, washing with deionized water to neutrality, and then drying under vacuum conditions at a temperature of 65° C. for 12 h, and then grinding to obtain a mixture precursor with an outer diameter of 8 nm to 15 nm and a length of ≤50 μm;

[0044] S3, placing the mixture precursor obtained in S2 into a tube furnace, raising the temperature from room temperature to 350°C at a heating rate of 2°C / min under a N2 atmosphere, then calcining at a constant temperature for 2h, and naturally cooling to room temperature to obtain a CNTs-CeO2 composite carrier;

[0045] S4, ultrasonically dispersing 50 mg of the CNTs-CeO2 composite carrier obtained in S3 into 30 mL of ethylene glycol to obtain a carrier mixed solution;

[0046] S5. To the carrier mixture obtained in S4, 6.25 mL of 0.0187 mol / L H2PdCl4 aqueous solution was added dropwise. After stirring for 4 h, the pH value was adjusted to 12 with 2 mol / L NaOH aqueous solution. The mixture was then transferred to a stainless steel kettle containing 100 mL of polytetrafluoroethylene lining and subjected to hydrothermal reaction at 120 °C for 4 h. After cooling to room temperature, the mixture was washed with deionized water for 4 times, and then washed with anhydrous ethanol for 4 times. The mixture was then dried at 70 °C under vacuum for 12 h. The Pd / CNTs-CeO2 nano-electrocatalyst with an average particle size of 4.13 nm was obtained, and was named Pd / CNTs-CeO2-3.

[0047] Comparative Example 1

[0048] The preparation method of the Pd / CNTs nano-electrocatalyst of this embodiment is as follows:

[0049] S1, ultrasonically dispersing 50 mg of multi-walled carbon nanotubes (MWCNTs) in 30 mL of ethylene glycol to obtain a carrier dispersion;

[0050] S2. Add 6.25 mL of 0.0187 mol / L H2PdCl4 aqueous solution to the carrier dispersion obtained in S4, stir for 4 h, adjust the pH value to 12 with 1 mol / L NaOH aqueous solution, transfer to a stainless steel kettle containing 100 mL of polytetrafluoroethylene lining, and perform hydrothermal reaction at 150°C for 4 h. After cooling to room temperature, wash with deionized water 4 times, then wash with anhydrous ethanol 4 times, and then dry under vacuum at 70°C for 12 h to obtain a Pd / CNTs nano-electrocatalyst with an average particle size of 4.0 nm, named Pd / CNTs.

[0051] Comparative Example 2

[0052] The preparation method of the CNTs-CeO2 nano-electrocatalyst of this comparative example is as follows:

[0053] S1, adding 0.2 g of multi-walled carbon nanotubes (MWCNTs) and 0.5 g of soluble cerium salt (cerium nitrate hexahydrate) to 12 mL of deionized water, and ultrasonically dispersing for 60 min to obtain a mixed solution;

[0054] S2, adjusting the pH value of the mixed solution obtained in S1 to 12 with a 1.0 mol / L KOH aqueous solution, stirring for 2 hours, washing with deionized water to neutrality, and then drying for 12 hours under vacuum conditions at a temperature of 65°C, and then grinding to obtain a mixture precursor with an outer diameter of 8 nm to 15 nm and a length of ≤50 μm;

[0055] S3, placing the mixture precursor obtained in S2 into a tube furnace, raising the temperature from room temperature to 300°C at a heating rate of 2°C / min under a N2 atmosphere, then calcining at a constant temperature for 2h, and naturally cooling to room temperature to obtain a CNTs-CeO2 composite carrier;

[0056] S4. Ultrasonic disperse 50 mg of the CNTs-CeO2 composite carrier obtained in S3 in 30 mL of ethylene glycol. After stirring for 4 hours, adjust the pH value to 12 with a 1 mol / L NaOH aqueous solution, transfer it to a stainless steel kettle containing 100 mL of polytetrafluoroethylene lining, and hydrothermally react at 150°C for 4 hours. After cooling to room temperature, wash it with deionized water 4 times, then wash it with anhydrous ethanol 4 times, and then dry it at 70°C under vacuum conditions for 12 hours to obtain a CNTs-CeO2 nano-electrocatalyst with an outer diameter of 8 nm to 15 nm and a length of ≤50 μm, named CNTs-CeO2.

[0057] Comparative Example 3

[0058] The preparation method of the reduced CNTs carrier of this comparative example is as follows:

[0059] S1. Ultrasonic dispersion of 50 mg multi-walled carbon nanotubes (MWCNTs) in 30 mL ethylene glycol to obtain a carrier dispersion. After stirring for 4 h, the pH value was adjusted to 12 with a 1 mol / L NaOH aqueous solution, and the dispersion was transferred to a stainless steel kettle containing 100 mL polytetrafluoroethylene liner. The dispersion was hydrothermally reacted at 150 ° C for 4 h. After cooling to room temperature, the dispersion was washed with deionized water for 4 times, then washed with anhydrous ethanol for 4 times, and then dried at 70 ° C for 12 h under vacuum conditions to obtain a reduced CNTs carrier.

[0060] Comparative Example 4

[0061] The preparation method of the Pd-CeO2 nano-electrocatalyst of this comparative example is as follows:

[0062] S1. Add 0.5 g of soluble cerium salt (cerium nitrite) to 12 mL of deionized water, and disperse by ultrasonication for 60 min. Then adjust the pH value to 12 with a 1.0 mol / L KOH aqueous solution, stir for 2 h, wash with deionized water until neutral, and then dry under vacuum at 65 ° C for 12 h, and then grind to obtain a precursor material with an outer diameter of 8 nm to 15 nm and a length of ≤50 μm.

[0063] S3, placing the precursor obtained in S2 into a tube furnace, raising the temperature from room temperature to 300°C at a heating rate of 2°C / min under a N2 atmosphere, then calcining at a constant temperature for 2h, and naturally cooling to room temperature to obtain a CeO2 metal oxide carrier;

[0064] S4, ultrasonically dispersing 50 mg of the CeO2 metal oxide carrier obtained in S3 into 30 mL of ethylene glycol to obtain a carrier dispersion;

[0065] S5. Add 6.25 mL of 0.0187 mol / L H2PdCl4 aqueous solution to the carrier dispersion obtained in S4, stir for 4 h, adjust the pH value to 12 with 1 mol / L NaOH aqueous solution, transfer to a stainless steel kettle containing 100 mL of polytetrafluoroethylene lining, and perform hydrothermal reaction at 150°C for 4 h. After cooling to room temperature, wash with deionized water 4 times, then wash with anhydrous ethanol 4 times, and then dry at 70°C under vacuum for 12 h to obtain a Pd / CeO2 nano-electrocatalyst with an average particle size of 4.25 nm, named Pd / CeO2.

[0066] Comparative Example 5

[0067] The commercial PtRu / C catalyst (Pt mass fraction is 30%, Ru mass fraction is 15%, and the atomic ratio of Pt to Ru is 1:1) was purchased from MacLean.

[0068] Example 4

[0069] The Pd / CNTs-CeO2 nano-electrocatalysts prepared in Examples 1-3, the Pd / CNTs prepared in Comparative Example 1, the CNTs-CeO2 prepared in Comparative Example 2, the reduced CNTs carrier prepared in Comparative Example 3, and the commercial PtRu / C catalyst in Comparative Example 5 were placed on the surface of a glassy carbon electrode (GCE) to electrocatalyze methanol oxidation in an alkaline environment.

[0070] Examples 1-3: Pd / CNTs-CeO2-1, Pd / CNTs-CeO2-2, Pd / CNTs-CeO2-3

[0071] Comparative Example 1: Pd / CNTs

[0072] Comparative Example 2: CNTs-CeO2

[0073] Comparative Example 3: CNTs carrier after reduction

[0074] Comparative Example 4: Pd / CeO2

[0075] Comparative Example 5: Commercial PtRu / C Catalyst

[0076] Before the test, the surface of the glassy carbon electrode was carefully polished with Al2O3 powder to make it regular, then washed with anhydrous ethanol and dried for use. Accurately weigh 2.0 mg of the catalysts in the above Examples 1 to 3 and Comparative Examples 1 to 4, and ultrasonically dispersed them in a mixture containing 50 μL of 0.5% Nafion membrane solution, 450 μL of anhydrous ethanol and 500 μL of ultrapure water to obtain catalyst ink, which was appropriately coated on the surface of the glassy carbon electrode and used as the working electrode for the test after it was completely dried. A conventional three-electrode system was used in the test, with a saturated calomel electrode (SCE) as the reference electrode and a platinum electrode as the counter electrode. The electrochemical properties of catalysts of different compositions were tested by cyclic voltammetry (CV), the electrolyte was 1.0 M KOH + 1.0 M CH3 OH, the scan rate was 50 mV / s, and the potential range was -0.9 to 0.3 V. The test results show that Pd / CNTs-CeO2-1 to Pd / CNTs-CeO2-3 (Examples 1-3) have the best electrocatalytic oxidation performance for methanol, and the mass specific activity of the catalyst is 2642.6 mA·mg -1 Pd ~3042.5mA·mg -1 Pd The reason why Pd / CNTs-CeO2-1 to Pd / CNTs-CeO2-3 have high activity is that the composite metal oxide carrier acts as a Pd anchoring point and also regulates the electronic structure of Pd. Specifically, part of the electrons at the interface between cerium oxide and Pd are transferred from cerium oxide to palladium, making the proportion of metallic Pd on the catalyst surface higher. The activity of Pd / CNTs (Comparative Example 1) is significantly lower, with a mass specific activity of 824.8 mA·mg -1 Pd The mass specific activity of Pd / CeO2 (Comparative Example 4) is 227.6 mA·mg -1 Pd , indicating that CeO2 alone as a carrier does not have good methanol oxidation activity, which may be due to the low conductivity of CeO2. However, CNTs-CeO2 (Comparative Example 2) and the reduced CNTs carrier (Comparative Example 3) have no electrocatalytic activity for methanol. At the same time, the commercial PtRu / C catalyst (Comparative Example 5) is used as a comparative example. Under the same test environment, the mass specific activity of PtRu / C is 2638.9mA·mg-1 Pt The potentials of Pd / CNTs-CeO2, Pd / CNTS, and PtRu / C for methanol electrocatalytic oxidation are all around -0.2 V, but the starting potentials and peak current densities are different. The specific values ​​are shown in Table 1.

[0077] Table 1 Performance test of catalysts prepared in Examples 1-3 and Comparative Examples 1-5

[0078]

[0079]

[0080] It can be clearly seen from the above table that the Pd nano-electrocatalyst loaded with CNTs-CeO2 has a lower initial peak potential for methanol oxidation and a higher peak current density. Compared with Pd / CNTs at the same loading, Pd / CNTs-CeO2 has better electrocatalytic performance. This is because the composite metal oxide regulates the electronic structure properties of the active metal Pd, thereby improving the adsorption and activation characteristics of methanol on the catalyst surface. The methanol oxidation activity of Pd / CeO2 is low, which is caused by the poor conductivity of CeO2. However, CNTs-CeO2 and the reduced CNTs carrier do not have the ability to electrocatalytically oxidize methanol.

[0081] Figure 1 is the X-ray diffraction (XRD) pattern of the CNTs-CeO2 composite support prepared in step S3 of Example 1, as shown in FIG. Figure 1 It can be seen that the characteristic peaks of the CNTs-CeO2 composite carrier are all located at 28.6°, 33.1°, 47.5°, 56.3°, 69.4° and 77.0° of the face-centered cubic structure (COD#01-078-0694) CeO2 crystal, corresponding to the (111), (200), (220), (311), (400) and (420) crystal planes of the face-centered cubic (fcc) structure of CeO2, respectively. The cerium oxide on the surface of the CNTs-CeO2 composite carrier is evenly dispersed, which can provide more anchoring points for the active metal, which is beneficial to improve the effective loading rate of the active metal Pd while ensuring the dispersion.

[0082] Figure 2 The transmission electron microscope (TEM) spectrum of the Pd / CNTs-CeO2 nano-electrocatalyst prepared in Example 1 is as follows: Figure 2 It can be seen that Pd / CNTs-CeO2 has a cluster structure and is relatively evenly dispersed, with an average particle size of 3.75nm.

[0083] Figure 3The cyclic voltammetry (CV) diagram of the Pd / CNTs-CeO2 nano-electrocatalyst prepared in Example 1 under 1.0M KOH + 1.0M CH3OH, the scan rate is 50mV / s, the potential range is -0.9-0.3V, as shown in FIG. Figure 3 It can be seen that Pd / CNTs-CeO2 has excellent electro-oxidation activity for methanol, and its current density is 3042.5 mA·mg at a potential of -0.108 V. -1 Pd .

[0084] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. An application of Pd / CNTs-CeO2 nano-electrocatalyst, characterized in that: The Pd / CNTs-CeO2 nano-electrocatalyst is used for the electrocatalytic oxidation of methanol in an alkaline environment; the potential range of the Pd / CNTs-CeO2 nano-electrocatalyst for the electrocatalytic oxidation of methanol is -0.9V to 0.3V, and the oxidation peak current is 2642.6mA·mg -1 Pd ~3042.5mA·mg -1 Pd ; The preparation method of the Pd / CNTs-CeO2 nano-electrocatalyst is as follows: S1, adding multi-walled carbon nanotubes and a soluble cerium salt to deionized water, ultrasonically dispersed for 60min to obtain a mixed solution; the amount ratio of multi-walled carbon nanotubes, soluble cerium salt and deionized water in the mixed solution in S1 is 0.2g: (0.5 to 3.5) g: 12mL; the soluble cerium salt in S1 is cerium nitrite or cerium nitrate hexahydrate; S2, adjusting the pH value of the mixed solution obtained in S1 to 11-13 with a 1.0 mol / L KOH aqueous solution, stirring for 2 h, washing with deionized water to neutrality, and then drying under vacuum conditions at a temperature of 65 ° C for 12 h, and then grinding to obtain a mixture precursor; the outer diameter of the mixture precursor in S2 is 8 nm to 15 nm, and the length is ≤50 μm; S3, placing the mixture precursor obtained in S2 into a tube furnace, raising the temperature from room temperature to 250°C~350°C at a heating rate of 2°C / min under a N2 atmosphere, then calcining at a constant temperature for 2h, and naturally cooling to room temperature to obtain a CNTs-CeO2 composite carrier; S4, ultrasonically dispersing the CNTs-CeO2 composite carrier obtained in S3 into ethylene glycol to obtain a carrier mixed solution; S5. Add a 0.0187 mol / L H2PdCl4 aqueous solution to the carrier mixture obtained in S4, stir for 4 hours, adjust the pH value to 12 with a 0.5 mol / L~2 mol / L NaOH aqueous solution, and then perform a hydrothermal reaction at a temperature of 120°C~170°C for 4 hours. After cooling to room temperature, wash with deionized water for 3~4 times, and then wash with anhydrous ethanol for 3~4 times, and then dry at a temperature of 70°C under vacuum for 12 hours to obtain a Pd / CNTs-CeO2 nano-electrocatalyst; the average particle size of the Pd / CNTs-CeO2 nano-electrocatalyst in S5 is 3.75nm~4.25nm.

2. The use of a Pd / CNTs-CeO2 nano-electrocatalyst according to claim 1, characterized in that: The dosage ratio of CNTs-CeO2 carrier and ethylene glycol in the carrier mixed solution described in S4 is 50 mg:30 mL.

Citation Information

Patent Citations

  • Sintering-resistant mosaic Pd@cerium dioxide nanotube catalyst and preparation method thereof

    CN110152658A

  • Preparation method of noble metal catalyst

    CN111151237A